1990
DOI: 10.1152/ajpendo.1990.258.4.e643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,25 dihydroxyvitamin D3 on isolated islets from vitamin D3-deprived rats

Abstract: Insulin release is impaired by vitamin D3 deficiency but can be restored by in vivo administration of 1,25 dihydroxyvitamin D3 [1,25(OH)2D3]. A direct influence of 1,25(OH)2D3 on the B-cell was studied in vitro with islets from 5-wk vitamin D3-deprived rats. This hormone (10(-12) to 10(-6) mol/l) added to the incubation medium had a stimulatory dose-dependent effect on insulin response to 8.3 mmol/l glucose 6 h later. Moreover, perifusion experiments performed after different times of incubation demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…Indeed, in previous studies we found that the beneficial influence of 1,25(OH) 2 D 3 on insulin release is only seen when the cells are stimulated and not in basal conditions. It is observable only after 6 h of induction (Billaudel et al 1990) and it cannot occur in the presence of cycloheximide, a transcriptional inhibitor (Bourlon et al 1999). Moreover, in this recent study, we show that the total islets proteins is not statistically modified by vitamin D 3 deficiency or by 1,25(OH) 2 D 3 , whereas the amount of newly synthesised labelled proteins during a glucose stimulation exhibits some variation.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Indeed, in previous studies we found that the beneficial influence of 1,25(OH) 2 D 3 on insulin release is only seen when the cells are stimulated and not in basal conditions. It is observable only after 6 h of induction (Billaudel et al 1990) and it cannot occur in the presence of cycloheximide, a transcriptional inhibitor (Bourlon et al 1999). Moreover, in this recent study, we show that the total islets proteins is not statistically modified by vitamin D 3 deficiency or by 1,25(OH) 2 D 3 , whereas the amount of newly synthesised labelled proteins during a glucose stimulation exhibits some variation.…”
Section: Discussionmentioning
confidence: 46%
“…12 M as a control as this dose is not considered to be biologically active (Billaudel et al 1990). Previous work has shown an identical level of islets insulin release for such 10 12 M controls and other controls using the vehicle alone (Bourlon et al 1999).…”
Section: Animals and Isolation Of Islets Of Langerhansmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, vitamin D deficiency impairs insulin synthesis (21,22), possibly via a reduced intracellular calcium concentration (23). The final statistical models presented in our study were adjusted for indices of glycemic control, such as glycated hemoglobin, fasting glucose, and insulin, so b-cell dysfunction and abnormal glucose homoeostasis may partly explain the increased risk of microvascular, but not macrovascular, disease, with decreasing blood concentrations of 25OH-D.…”
Section: Discussionmentioning
confidence: 99%
“…1,25(OH) 2 D 3 has multiple effects that can explain this protection against diabetes. First, there is the effect on the b cell: 1,25(OH) 2 D 3 influences b cell calcium metabolism and eventually insulin secretion [33][34][35], and it has been described that 1,25(OH) 2 D 3 protects against IL-1b-induced b cell dysfunction [36]. Second, 1,25(OH) 2 Apoptosis is expressed as percentage TUNEL-positive cells (b).…”
Section: Discussionmentioning
confidence: 99%